2005
DOI: 10.1590/s0482-50042005000100002
|View full text |Cite
|
Sign up to set email alerts
|

Osteonecrose em pacientes com lúpus eritematoso sistêmico

Abstract: Osteonecrosis is a relatively common complication in systemiclupus erythematosus (SLE) patients. Objective: To evaluate the possible risk factors associated with osteonecrosis in SLE patients. Methods: SLE patients [according to American College of Rheumatology (ACR) criteria] who presented osteonecrosis were included in this study. SLE patients with no symptomatic osteonecrosis constituted the control group. Osteonecrosis was confirmed by radiographic evaluation, bone scintigraphy and/or magnetic resonance im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 24 publications
(67 reference statements)
0
3
0
2
Order By: Relevance
“…15 In fact, cardiac involvement in SLE has been described between 50% and 89% in several studies throughout the course of the disease, with pericarditis being the most common manifestation. 16…”
Section: Discussionmentioning
confidence: 99%
“…15 In fact, cardiac involvement in SLE has been described between 50% and 89% in several studies throughout the course of the disease, with pericarditis being the most common manifestation. 16…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, there are numerous publications showing the occurrence of iatrogenic events that can be classified as accidental and do not imply poor medical practice. 5 Examples of this situation would be the drug-induced rheumatic manifestations, 6,18,19 steroid-induced osteonecrosis, 20 drug-induced lupus-like syndromes, 21,22 cutaneous drug reactions, 23 side effects of drugs used in rheumatic diseases 24 and steroid-induced osteoporosis. 25 In regard to cutaneous drug reactions and drug reactions in hospitalized patients, a meta-analysis 26 demonstrated a 6.7% incidence of severe reactions defined as those requiring hospitalization or associated with deaths.…”
Section: Iatrogenesis In Rheumatologymentioning
confidence: 99%
“…Outras patologias menos comuns, 14 15 16 17 18 19 como doença de Gaucher, doença de Caisson, disbarismo por mergulhos em águas profundas, assim como HIV, radioterapia, gravidez, tabagismo e gota também podem levar a ONCF. Um estudo recente demonstrou que, em casos idiopáticos, alterações acetabulares com menor cobertura da cabeça femoral podem estar relacionadas à ONCF.…”
Section: Introductionunclassified
“…Other less common pathologies, 14 15 16 17 18 19 such as Gaucher disease, Caisson disease, dysbarism from deep water diving, as well as HIV, radiation therapy, pregnancy, smoking and gout can also lead to ONFH. A current study has shown that, in idiopathic cases, acetabular alterations with less coverage of the femoral head may be related to ONFH.…”
Section: Introductionmentioning
confidence: 99%